Biological enzyme treatment of starch-based lithium-ion battery silicon-carbon composite. (5th November 2020) - Wei, Runhong; Xu, Ruhui; Zhang, Keyu; Liang, Feng; Yao, Yaochun
Abstract: Silicon/carbon composites have the disadvantages of large volume expansion and high cost, which limits their commercial application. In this study, green and economic starch was used to prepare porous starch (PS) under the action of enzymes, and then nano-silica was embedded in the PS. A PS based carbon/silicon/carbon composite was prepared by coating and carbonizing the starch slurry, which can alleviate the volume expansion of silicon. The results show that the anode composite material with 20% silicon content has a high initial capacity of 869 mAh g −1 and an initial Coulombic efficiency of 66% at 0.2 A g −1, and the specific capacity is maintained 450 mAh g −1 after 100 cycles. When the silicon content reaches 30%, the reversible capacity of the composite is 1490 mAh g −1 at a current density of 0.2 A g −1, and the capacity remains 850 mAh g −1 after 100 cycles. Its excellent properties and stability are attributed to the abundant porosity of the carbon in the starch derived layer, which improves the structural stability and electrochemical kinetics. This method provides a reference for the sustainable and environmental protection of lithium-ion battery anode materials.